1990
DOI: 10.1080/00223891.1990.9674064
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Depression in an Employment Setting

Abstract: This study extends the literature on sex differences in depression to an employment setting, using Minnesota Multiphasic Personality Inventory (MMPI; T and raw scores) and Depression (D) 30 measures. In contrast to previous findings, no gender differences remained on any of the measures after the effects of salary, age, education, and job classification had been taken into account. Findings replicated earlier results showing depressed males to have greater difficulty with concentration and motivation than depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lower skilled occupations, lower occupational levels and blue-collar workers were associated with more anxiety and/or depression (Kleppa et al, 2008 ; Maffeo et al, 1990 ; Rose et al, 2006 ). The Maffeo et al ( 1990 ) study found that higher level managers had significantly fewer symptoms of depression than other occupation categories including trade and labour.…”
Section: Resultsmentioning
confidence: 99%
“…Lower skilled occupations, lower occupational levels and blue-collar workers were associated with more anxiety and/or depression (Kleppa et al, 2008 ; Maffeo et al, 1990 ; Rose et al, 2006 ). The Maffeo et al ( 1990 ) study found that higher level managers had significantly fewer symptoms of depression than other occupation categories including trade and labour.…”
Section: Resultsmentioning
confidence: 99%
“…Seven [15,16,18,20,21,23,24] studies examined gender differences in severity of depression. Four of those [16,20,21,24] found no gender differences and 3 studies [15,18,23] found that women get higher total scores on depression rating scales than men. In table 1, the studies performed in clinical samples are summarized.…”
Section: Studies Performed In Broader Samples Of Depressive Patientsmentioning
confidence: 99%
“…Unsurprisingly, depression in men has been found to be associated with a number of features that are not found on the list of traditional diagnostic criteria. For example, depression in men has been found to be associated with rigid adherence to traditional masculine gender roles (Heifner, 1997), masculine gender role conflict (Good & Wood, 1995), work, concentration, and performance-related difficulties (Maffeo, Ford, & Lavin, 1990;Vredenburg, Krames, & Flett, 1986), and increased interpersonal conflict (Williamson, 1987). In addition to these gender role-related associations, young men with a history of dysthymia were found to use projective and outwardly directed aggressive defenses and were perceived by others as antagonistic and disagreeable (Gjerde, Block, & Block, 1988).…”
Section: Depression In Menmentioning
confidence: 99%